The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1515/cppm-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Process Modelling, Thermodynamic Analysis and Optimization of Dry Reforming, Partial Oxidation and Auto-Thermal Methane Reforming for Hydrogen and Syngas production

Abstract: In this work, process modelling, thermodynamic analysis and optimization of stand-alone dry and partial oxidation reforming of methane as well as, the auto-thermal reforming processes were investigated. Firstly, flowsheet models were developed for both the stand-alone systems and auto-thermal reforming process using ASPEN HYSYS ® . Furthermore, thermodynamic studies were conducted for the stand-alone and auto-thermal reforming processes for temperatures range of 200-1000°C and pressure range of 1-3 bar using G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The methane dry reforming process is highly endothermic [30]. Therefore, the reaction is favored by a high temperature >900 K [31]. Although, the mechanism of the methane dry reforming reaction is Catalysts 2019, 9, 738 4 of 20 strongly dependent on the nature of the catalyst, it is generally believed that the reaction commences with the activation of CH 4 and CO 2 being adsorbed on the catalyst active sites [32].…”
Section: Interaction Effect Of Process Parameters On the Rate Of H 2 mentioning
confidence: 99%
“…The methane dry reforming process is highly endothermic [30]. Therefore, the reaction is favored by a high temperature >900 K [31]. Although, the mechanism of the methane dry reforming reaction is Catalysts 2019, 9, 738 4 of 20 strongly dependent on the nature of the catalyst, it is generally believed that the reaction commences with the activation of CH 4 and CO 2 being adsorbed on the catalyst active sites [32].…”
Section: Interaction Effect Of Process Parameters On the Rate Of H 2 mentioning
confidence: 99%
“…30 Furthermore, Gibbs free energy minimization methods via Aspen Hysys was developed to numerically investigate the thermodynamic analysis and optimization of dry and partial oxidation and auto-thermal (combined DR and POX) reforming processes at temperatures range of 200-1000 C and pressure range of 1-3 bar. 31 The effect of several parameters including the process temperature, operating pressure, catalyst weight loading, and mass ratio of feed gas on the process of steam reforming of NG has been studied to perform hydrogen production. The kinetic-based simulation model of steam methane reforming and WGS reaction for hydrogen production was performed in Aspen Plus.…”
Section: Introductionmentioning
confidence: 99%
“…The conversions of CH 4 and CO 2 increased with the temperature increase, but the rate of conversion increase was slower at higher 2B) (Chen et al, 2017). Ayodele and Cheng (Ayodele and Cheng, 2015) found that the yield of H 2 and CO increased with increased temperature from 200 C to 1,000 C. However, the syngas formation was not thermodynamically favored at 200-400 C (Ayodele and Cheng, 2015).…”
Section: Dry Reforming Of Biogas To Syngasmentioning
confidence: 96%